Tracing our computing roots : Nanyang University Lee Kong Chian Computer Centre and the department of Computer Science - Chan, Jia Hui (2016)
There has been a lack of scholarship written on the importance education played in the history of computing in Singapore. The pioneering effort of the Nanyang University Lee Kong Chian Computer Centre and the Department of Computer Science at Nanyang University elucidate the crucial role education played in the early development of computers and the field of computing in Singapore. This dissertation explores the conditions of the formation of the two institutions and the contributions they made to the industry and the society with regards to computers and computing. The foresight of the pioneers, the efforts made to promote computers and computing, and later on, the support of the government are crucial factors for the foundations of the computer industry in Singapore. Lastly, this paper also seeks to contribute to the history of computing in Singapore in the gap years of the late 1960s to the 1970s of existing scholarships.